Enriched Acoustic Environment after Noise Trauma Reduces Hearing Loss and Prevents Cortical Map Reorganization - Noreña, Arnaud J. (J Neurosci, 2005)
Exposure to sound of sufficient duration and level causes permanent damage to the peripheral auditory system, which results in the reorganization of the cortical tonotopic map. The changes are such that neurons with pre-exposure tuning to frequencies in the hearing loss range now become tuned to frequencies near the near-normal lower boundary of the hearing loss range, which thus becomes over represented. However, cats exposed to a traumatizing noise and immediately thereafter placed for a few weeks in an enriched acoustic environment presented a much-restricted hearing loss compared with similarly exposed cats that were placed for the same time in a quiet environment. The enriched environment spectrally matched the expected hearing loss range and was ∼40 dB above the level of the expected hearing loss. The hearing loss in the quiet environment-reared cats ranged from 6 to 32 kHz with the largest loss (on average, 40 dB) ranging from 24 to 32 kHz. In contrast, the hearing loss in the enriched-environment cats was restricted to 6-8 kHz at a level of, on average, 35 dB and with 16-32 kHz having normal thresholds. Despite the remaining hearing loss for the enriched-environment cats in the 6-8 kHz range, plastic tonotopic map changes in primary auditory cortex could no longer be demonstrated, suggesting that the enriched acoustic environment prevents this reorganization. This finding has implications for the treatment of hearing disorders, such as tinnitus, that have been linked to cortical tonotopic map reorganization.